Sexual function and sexual activity in young total hip arthroplasty Chinese patients: A retrospective cohort study - Yang, Daishui; Zhang, Jie; Zhang, Kexin; Zhou, Yanlin; Peng, Xiao; Wang, Ling; Liu, Tang (Frontiers in Surgery, 2023)
Abstract Introduction: As an essential component of quality of life, there is limited evidence of sexual function (SF), especially for young patients before and after total hip arthroplasty (THA). This study aims to enhance understanding of SF status and assess patient perspectives before and after THA. Methods: A total of 109 patients who received THA were recruited into our retrospective cohort study. To assess the SF status before and after THA, patients were required to fulfil a standardized SF questionnaire [Female Sexual Function Index (FSFI) or Brief Sexual Function Inventory (BSFI) for males], as well as a specifically designated questionnaire regarding perspectives towards sexual activity and attitudes to sexual-related information. Results: Both total average scores of FSFI and BSFI were higher post-THA. For female patients, the FSFI scores were significantly higher in the domain of desire, orgasm and satisfaction (p<0.05). For male patients, the BSFI scores were also improved in the sex drive and satisfaction domain post-operation (p<0.05). A large proportion of the patients (64.22%) reported sexual activity difficulty preoperatively, primarily due to restricted motion (82.86%) and hip pain (74.29%). After the successful procedure, there was a reduction in patients’ sexual activity difficulty degree post-THA (39.45%), mainly attributed to less pain (72.09%) and greater mobility (79.07%). In addition, subgroup analysis results indicated that gender and severity of hip stiffness and pain were crucial factors which could affect the patient’s SF status. Furthermore, the majority of patients reported that they desired information concerning sexual activity, but only 12.84% of patients were informed well. Patients preferred channels to acquire sexual-related information was a booklet (65.59%, n=61), followed by surgeon and nurse informed. The most concerning questions regarding the sexual activity of patients were the time of recovery (90.32%) and safe postures (76.34%). Conclusion: The majority of men and women who underwent THA reported their SF status return to baseline or improved, mainly attributable to less pain and greater mobility. Age and the severity of hip pain/ stiffness were the factors which could affect patients’ SF status. Sexual education for young THA patients is needed due to lacking related information during hospitalization.